Soft skills requirements in mobile applications development employment market. (5th July 2019) - Jia, Jingdong; Chen, Zupeng; Liu, Xi
The soft skills of developers have a major influence on the quality of software product and project. However, which soft skills are important for mobile applications development remains unknown. Additionally, it is necessary to examine the differences of soft skills requirements between traditional software and mobile applications development. In this article, based on text mining including word segmentation, similarity calculation and clustering analysis, we analyse lots of advertisements, and extract 13 categories of soft skills requirements for mobile applications development. We also compare the categories with those for traditional software development. We find that communication and teamwork are still the most important two soft skills. However, fast learning is more important for mobile developers, and we identified four soft skills that are not proposed before. Additionally, season has a minor impact on soft skills requirements of mobile applications development.